Spaces of transition: Kantarcılar as a microcosm of urban change in late Ottoman Istanbul - Turna, Nalan; Ersoz, Burcak (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This article examines Kantarc & imath;lar's transformation in late Ottoman Istanbul as a microcosm of urban change. It argues that micro-urban modernity emerged not only through state reforms but also through the interactions of everyday practices, informal networks, and shared spaces. The article traces Kantarc & imath;lar's shift from a manufacturing district to a commercially diversified, mixed-use area. Drawing on Henri Lefebvre's production of space framework, it shows how the perceived (spatial practice), conceived (representations of space), and lived (representational spaces) intersect in shaping Kantarc & imath;lar's dynamics. Using Ottoman archival records, maps, trade yearbooks and newspapers, the article demonstrates the mutual constitution of formal modernization and informal practices in producing Istanbul's urban fabric at the grassroots, with Kantarc & imath;lar as a focal case. It also positions Kantarc & imath;lar as a comparative case for analyzing urban modernity across other late Ottoman and post-Ottoman cities, thereby enriching debates on space, society and modernity.
Keywords: Late Ottoman period; Istanbul; Kantarc & imath; lar; micro-urban modernity; migration; Area Studies